Effects of vascular endothelial growth factor receptor-1 inhibition on vasculogenic mimicry and the metabolic profile of breast cancer cells in vitro - Mabeta, Peace (University of Pretoria, 2023)
Thesis (PhD (Physiology))--University of Pretoria, 2023.